Analisis Akad Ju’alah pada Sistem Affiliate TikTok Shop Perspektif Hukum Ekonomi Syariah - Haurah Nur Rahmah; Najwah Fadillah (Prodi Ahwal Asy Syahsiyah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2025)
The rapid development of digital commerce has created new business models in social media-based marketplaces, one of which is the affiliate program on TikTok Shop. This program allows users to earn commissions by promoting products through unique links integrated with TikTok content. This research aims to analyze the practice of the TikTok Shop affiliate system from the perspective of Islamic economic law, particularly through the lens of the ju’alah contract as regulated in DSN-MUI Fatwa No. 62/DSN-MUI/XII/2007. This study uses a qualitative approach with a juridical-normative method supported by literature review and observation of TikTok Shop affiliate practices. The results indicate that the TikTok Shop affiliate system structurally fulfills the pillars of the ju’alah contract, namely the existence of ja’il (seller), maj’ul lah (affiliator), ‘amal (promotional work), and ‘iwadh (commission). However, several aspects need attention to ensure compliance with sharia principles, including transparency of commissions, clarity of completion criteria, the prohibition of gharar in payment mechanisms, and avoidance of tadlis in product promotion. From the perspective of Islamic economic law, this practice is permissible as long as it is carried out within the framework of sharia principles and avoids deviations such as misleading promotions and excessive uncertainty.